Impact of Volcanic Ash on Acidity, Mineral and Nutrient Content of Creeks and Soils Following the Montserrat Soufriere Hills Eruptions - Orien L Tulp; Frantz Sainvil; Rolando Branly; Andrew Sciranka; Roberto Guibert; George P Einstein (Geography, Earth Science and Environment: Research Highlights Vol. 9, 2025)
Volcanic activity occurs in hundreds of locations on the planet, extending from the far reaches of Iceland in the Northern hemisphere to the south Pacific ‘rim of fire’ and beyond. Montserrat’s once-deemed near-extinct Soufriere Hills volcano roared to life after many decades of dormancy in 1995 and continued belching its plumes into the atmosphere and its volcanic (volcano) ash flow into the surrounding lower elevations for more than a decade, forcing over half of the population to evacuate to safer domains. The volcano finally experienced relaxation of the most aggressive phases of eruptive activity in 2010. Volcanic eruptions typically deliver enormous amounts of gases, minerals and ash residues to the nearby land and streams patenting contaminating the surrounding environment. Because agricultural soils and potable water supplies provide a major source of minerals known to be essential for plant and animal health, it was of interest to determine the pH, mineral, and nutrient composition of the creeks and surroundings following Montserrat’s volcanic eruption. The volcano wreaked severe havoc and irreparable damage to the geography and ecosystems, and created a serious immediate and chronic health risk to the remaining inhabitants of the Island. The active pyroclastic ash flow reached temperatures of 1500 °F or more and progressed down the hillsides at speeds often exceeding 80 mph. The extreme temperatures of the ash flow caused instant incineration and virtual destruction of everything in its path, while the gaseous and particulate-laden plume reached altitudes of 7 miles (10.7 km), impacting air quality and aircraft navigation in the region. A total of 19 individuals became entrapped in the lava flow and perished quickly as a direct result of the volcanic eruption. Volcanic soils derive from deeper layers of the Earth’s surface and are notoriously rich in mineral nutrients representative of those deep mineral deposits. While virtually all combustible objects in the path of the raging ash flow become incinerated within minutes, the aftermath of the eruptions delivers the mineral-rich constituents over a wide swath of the surrounding geography, often reaching miles from the volcanic origin. Soils and consumable water sources are well known to provide a reliable community source of essential minerals in human nutrition, and in their chronic absence, numerous pathologic sequela may develop. To determine the mineral content of surrounding surface soils, samples of surface ash layers and nearby creeks were obtained from 7 regions and 3 free-flowing creeks and subjected to mineral analysis. The surface ash specimens contained abundant amounts of the nutrients Iron, Calcium, Sodium, Magnesium, Sulfur, and non-nutrient Aluminum, intermediate amounts of potassium, Phosphorus, and Manganese, and small amounts of Boron, Copper and Zinc. Creek water runoff originating from higher elevations was consistently acidic with a healthy mean pH of 5.1, and contained smaller proportions of the same minerals, reflective of their relative effective solubility in the acidic water. Thus, the volcanic ash flow while devastating to the environment and public health in the immediate aftermath, provided numerous minerals important to plant and animal nutrition and to human health and health water sources which contributed to the longer-term reinstitution of edible plants and to the recovery of the vibrant lush greenery of the Emerald Isle of the Caribbean.